Effectiveness of transcutaneous electrical nerve stimulation in improving cognitive function in older adults with cognitive impairment: a systematic review and meta-analysis - Chan, Nga Huen; Ng, Shamay S. M. (Frontiers in Neurology, 2025)
BackgroundTranscutaneous electrical nerve stimulation (TENS), which involves the application of electrical stimulation to peripheral nerves, is used to improve or maintain cognitive function. Although many studies have examined the effect of TENS on cognition over the past 20 years, a comprehensive review and meta-analysis on this topic is lacking. This study aimed to evaluate the efficacy of TENS in improving cognitive function in older adults with cognitive impairment.MethodsA systematic search was performed in six electronic databases (CINAHL, Cochrane Library, Embase, Medline, PubMed, and Web of Science) to identify relevant studies published until May 2024. Moreover, the registered clinical trials, forward citation searches, and reference lists of identified publications were reviewed to identify additional relevant studies. Randomised controlled trials investigating the effect of TENS on cognitive function in older adults with cognitive impairment were included.ResultsSeven studies including 247 older adults with cognitive impairment were included. The findings revealed a trend towards positive effects of TENS on face recognition memory [mean difference (MD) = 1.19, 95% confidence interval (CI) = −0.13 to 2.52] and verbal fluency [standardised MD (SMD) = 0.29, 95% CI = −0.01 to 0.59] when compared with placebo stimulation (control condition). TENS demonstrated a significant positive delayed effect on visual memory (SMD = 0.55, 95% CI = 0.11 to 0.98). Subgroup analysis indicated that TENS applied on the concha was more effective than that applied on the spinal column and earlobe in improving verbal memory in the delayed condition.ConclusionA positive trend of immediate effect and a significant long-term effect on some cognitive domains were found after applying TENS in in older adults with cognitive impairment. Future studies with robust experimental designs and adequate sample sizes are warranted to investigate the efficacy of TENS in improving cognitive function.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42023408611, PROSPERO: CRD42023408611.